Understanding congressional coalitions: A discourse network analysis of congressional hearings for the Every Student Succeeds Act - Yinying Wang (Arizona State University, 2020)
The purpose of this study is to investigate policy coalitions of the Every Student Succeeds Act (ESSA) at U.S. congressional hearings. This study is grounded in the advocacy coalition framework, which argues that advocacy coalitions are forged by policy actors who have similar policy preferences. To identify the coalitions, according to the policy claims articulated by policy actors, discourse network analysis was performed to examine 30 testimonies in the congressional hearings on ESSA since its passage in 2015. The policy actors fall into eight categories: (1) federal administrative and executive offices, (2) state administrative and executive offices, (3) teachers unions, (4) interest groups, (5) superintendents, (6) teacher, (7) education professor, and (8) Congress members. The results of discourse network analysis suggest four coalitions based on the actors' policy claims on (1) equity, (2) assessment and accountability, (3) states have changed/passed legislation to align the state accountability systems with ESSA goals, and (4) the U.S. Department of Education's state plan approval was inconsistent with the ESSA statutory provisions. The findings provide timely insights into the ongoing process of ESSA implementation at the federal, state, and local levels.